Understanding School-Based Interpersonal Relationships: the Case of Morning Greetings in a Thai-Muslim School Context - Ubaidillah, Ubaidillah; Nurul Aini; Yah Nursuraiya (UIII Press, 2025)
Morning greeting rituals are a common yet culturally rich practice in many schools, serving as more than simple pleasantries. In the Thai-Muslim context of Adameesoksavittaya School in Krabi, these daily interactions reflect deeper values of respect, identity and community. This research delves into an investigation of the socio-cultural dynamics surrounding morning greeting gestures at Adameesoksavittaya School in Krabi, Thailand. The objectives of the research are to observe the significance of morning greetings within the school’s cultural context and to explore how these gestures contribute to interpersonal relationships among students and staff. Employing a qualitative ethnographic approach, data was gathered through participant observation, interviews and document analysis. The findings reveal rich cultural norms and social interactions embedded in the morning greeting rituals, that these gestures serve as more than mere formalities; they embody respect, solidarity and communal belonging within the school community. The study also elucidates the nuanced variations in greeting gestures based on culture. The main argument underscores the importance of recognizing the sociocultural intricacies inherent in seemingly mundane daily practices. Understanding and respecting these customs not only foster a sense of inclusivity and mutual respect but also contribute to the overall well-being and cohesion of the school community. This research provides valuable insights into the role of cultural practices in shaping social dynamics within educational settings.